Metabolic profiling reveals genotype-associated alterations in carotenoid content during banana postharvest ripening. (1st March 2023) - Sheng, Ou; Yin, Zhibin; Huang, Wenjie; Chen, Mengyu; Du, Mingyi; Kong, Qian; Fernie, Alisdair R.; Yi, Ganjun; Yan, Shijuan
Highlights: Metabolite profiling of AAA-, AAB-, ABB-genome banana during postharvest ripening. Accumulation of carotenoids and amino acids show genotype-dependent patterns. High carotene levels are correlated with low levels of glycolysis-derived AAs. High carotene levels are correlated with high levels of TCA cycle-derived AAs. Abstract: Banana fruits have attracted considerable attention for health-promoting effects attributed to ubiquitous functional metabolites. However, genotype-dependent accumulation patterns of carotenoids in banana remain largely unclear. Here, we performed a systematic metabolomic investigation of 18 banana cultivars of the AAA, AAB, or ABB genome groups. Our results indicate that the levels of soluble sugars increase during postharvest ripening regardless of genotype, whereas amino acids (AAs) and tricarboxylic acid (TCA) cycle-derived organic acids display genotype-dependent patterns. The levels of AAs derived from the glycolytic pathway increased, whereas those derived from the TCA cycle significantly decreased during ripening. The carotenoid composition in banana pulp was genotype-specific, and the contents of α-carotene were the highest in AAA-genome bananas. Moreover, high α-carotene and β-carotene contents in banana were correlated with elevated levels of TCA cycle-derived AAs and decreased levels of glycolysis-derived AAs. Taken together, these findings provide a comprehensive understanding of genotype-associated carotenoid accumulation, thereby facilitating the breeding of future high carotenoid banana cultivars.